Phalloplasty in Female-to-Male Transsexuals by Gottlieb and Levine's Free Radial Forearm Flap Technique—A Long-Term Single-Center Experience Over More than Two Decades - Wirthmann, Anna E.; Majenka, Pawel; Kaufmann, Melanie C.; Wellenbrock, Sascha V.; Kasper, Lara; Hüttinger, Susanne; Djedovic, Gabriel; Bozkurt, Ahmet; Sohn, Michael; Rieger, Ulrich M. (Journal of Reconstructive Microsurgery, 2018)
Background The free radial forearm flap phalloplasty is the most utilized method for penile reconstruction. Among the techniques described in the literature, evidence for the flap design after Gottlieb and Levine is poor.Methods From January 1993 until December 2015, 402 phalloplasties were performed in our clinic. Among the 247 free radial forearm flap phalloplasties, 232 free radial forearm flap phalloplasties were performed after Gottlieb and Levine in 229 patients. Operation and patient-specific characteristics were evaluated.Results This study presents the highest number of free radial forearm flap phalloplasties after Gottlieb and Levine. The rate of total flap failure was 3%; 46% of the patients were heavy smokers. Urinary fistulae and strictures are common. The revision rate for urinary fistulae and/or strictures was 1.3 per patient. The number of postoperative complications, such as bleeding (14.2%), thrombosis of the flap requiring revision (11.2%), or delayed wound healing (16.8%) was considering the high rate of nicotine abuse (45.9%) reasonable.Conclusion The free radial forearm phalloplasty in the design by Gottlieb and Levine is well established at our institution and has proven safe and reliable since 1993. The operative results are satisfactory for both patients and surgeons even in the presence of relevant comorbidities and heavy smoking. We acknowledge the long ordeal and psychological pressure that our patients suffer from, before presenting in our outpatient clinic.
Keywords: smoking; Gottlieb and Levine; fistula